AMBULATORY BLOOD PRESSURE IN RELATION TO PLASMA AND URINARY MANGANESE. (April 2021) - Zhang, Zhen-Yu; Carmeli, Cristian; Ponte, Belen; Pruijm, Menno; Ackermann, Daniel; Ehret, Georg; Guessous, Idris; Petrovic, Dusan; Pechère-Bertsc, Antoinette; Vogt, Bruno; Martin, Pierre -Yves; Burnier, Michel; et al.
Abstract : Objective: The association of blood pressure (BP) with manganese, an essential trace element required for human health, remains poorly studied. Design and method: In 734 randomly recruited Swiss participants (mean age, 47.5 years; 51.4% women), we related ambulatory BP to two biomarkers, plasma manganese (pMn) and the urinary manganese excretion (uMn). To allow for diurnal variation, we assessed BP and uMn over 24 h and during wakefulness and sleep, using split urine samples. Results: 24 h, day- and night-time systolic/diastolic BPs averaged 119.8/78.1, 123.8/81.2 and 107.0/68.3 mm Hg; the corresponding medians uMn were 199.5, 83.0, 51.5 umol and median pMn 0.52 ug/L. In analyses dichotomized by the median of the biomarkers, greater pMn was associated with higher 24 h systolic/diastolic BP (+4.1/+ 2.3 mm Hg; P<= 0.0003), greater daytime uMn with lower daytime BP (3.5/ 1.9 mm Hg; P<= 0.0067) and greater nighttime uMn with higher nighttime BP (+2.9/+ 1.2 mm Hg; P<= 0.046). In multivariable-adjusted analyses, significance (P<= 0.030) was retained for the positive association of 24 h and daytime diastolic BP with pMn and for systolic BP in relation to uMn at night. The association sizes for a twofold increment in the biomarkers amounting to 0.77 mm Hg (95% confidence interval [CI], 0.08–1.47 mm Hg), 0.97 (CI, 0.20–1.76) and 1.33 (CI, 0.20–2.50 mm Hg), respectively. Conclusions: In conclusion, there were positive associations between diastolic BP and pMn over 24 h and during daytime and between systolic BP and uMn at night.